High correlations between levels of consumption and mortality related to strong prescription opioid analgesics in British Columbia and Ontario, 2005 – 2009. (14th January 2013) - Fischer, Benedikt; Jones, Wayne; Rehm, Jürgen
ABSTRACT Purpose Prescription opioid analgesic (POA)‐related burden of disease – including mortality – is high and constitutes a major public health problem in the US and Canada. Associations between the overall levels of POA consumption and key related morbidity indicators in the population have been demonstrated. We examined potential correlations between levels of consumption of four commonly used POAs and related mortality in British Columbia (BC) and Ontario. Methods We investigated the correlation between annual population standardized rates of fentanyl, hydromorphone, morphine and oxycodone‐related mortality (based on provincial coroners' data) and the annual Defined Daily Doses per 1000 population/day for each of the drugs dispensed (based on representative retail pharmacy sales data) in the two provinces, 2005‐2009. Results Death rates increased for three (Ontario) and two (BC) of the four POA drugs; the rate of deaths for each POA drug was consistently higher in the jurisdiction with higher use levels. For each drug, strong correlations (range 0.83 to 0.97; p < 0.003) were found between POA use and mortality levels; consistent within‐province correlations were found for two drugs (hydromorphone and oxycodone). Conclusions Our findings of strong correlations between select POA use and mortality levels reflect similar evidence from elsewhere on correlations between POA consumption and morbidity or mortality indicators. In the context of high and increasing levels of POA consumption in Canada, efforts to reduce POA‐related mortality may require a comprehensively revised approach towards more appropriate and safer prescribing to reduce POA use volumes together with more effective monitoring of POA medications. Copyright © 2013 John Wiley & Sons, Ltd.